Tracing attosecond electron emission from a nanometric metal tip - Dienstbier, Philip; Seiffert, Lennart; Paschen, Timo; Liehl, Andreas; Leitensdorfer, Alfred; Fennel, Thomas; Hommelhoff, Peter (Nature, 2023)
Solids exposed to intense electric fields release electrons through tunnelling. This fundamental quantum process lies at the heart of various applications, ranging from high brightness electron sources in d.c. operation to petahertz vacuum electronics in laser-driven operation. In the latter process, the electron wavepacket undergoes semiclassical dynamics in the strong oscillating laser field, similar to strong-field and attosecond physics in the gas phase. There, the subcycle electron dynamics has been determined with a stunning precision of tens of attoseconds, but at solids the quantum dynamics including the emission time window has so far not been measured. Here we show that two-colour modulation spectroscopy of backscattering electrons uncovers the suboptical-cycle strong-field emission dynamics from nanostructures, with attosecond precision. In our experiment, photoelectron spectra of electrons emitted from a sharp metallic tip are measured as function of the relative phase between the two colours. Projecting the solution of the time-dependent Schrödinger equation onto classical trajectories relates phase-dependent signatures in the spectra to the emission dynamics and yields an emission duration of 710 ± 30 attoseconds by matching the quantum model to the experiment. Our results open the door to the quantitative timing and precise active control of strong-field photoemission from solid state and other systems and have direct ramifications for diverse fields such as ultrafast electron sources, quantum degeneracy studies and sub-Poissonian electron beams, nanoplasmonics and petahertz electronics.
Keywords: Nanophotonics and plasmonics; Quantum mechanics; Ultrafast photonics